PENGARUH BUDAYA SAFETY DAN PELATIHAN KERJA TERHADAP RISIKO TINGKAT KECELAKAAN KERJA DI DINAS PEMADAM KEBAKARAN KABUPATEN BULELENG - Kusuma, Gusti Putu Eka; Desi Ariani, Kadek (Jurnal Daya Saing, 2025)
This research aims to analyze the influence of safety culture and work training on the risk of workplace accidents rate in Buleleng Regency Fire Departement. The research uses quantitative data obtained through measuring employee participation in safety prosedures and training indicators.The result of the study show that work training has a significant impact on reducing the risk of workplace accidents. which means that every increase in work training by 1 unit will recude the risk of workplace accidents by 0,373 units. Additionally, this study also identifies challenges in assessing the performance improvement of training participants and its impact on the company as a whole.